Keeping up with the guidelines: design changes to the STREAM stage 2 randomised controlled non-inferiority trial for rifampicin-resistant tuberculosis - Ruth L. Goodall; Karen Sanders; Gay Bronson; Meera Gurumurthy; Gabriela Torrea; Sarah Meredith; Andrew Nunn; I. D. Rusen; on behalf of the STREAM Trial Team (Trials, 2022)
Abstract Results from the STREAM stage 1 trial showed that a 9-month regimen for patients with rifampicin-resistant tuberculosis was non-inferior to the 20-month regimen recommended by the 2011 WHO treatment guidelines. Similar levels of severe adverse events were reported on both regimens suggesting the need for further research to optimise treatment. Stage 2 of STREAM evaluates two additional short-course regimens, both of which include bedaquiline. Throughout stage 2 of STREAM, new drug choices and a rapidly changing treatment landscape have necessitated changes to the trial’s design to ensure it remains ethical and relevant. This paper describes changes to the trial design to ensure that stage 2 continues to answer important questions. These changes include the early closure to recruitment of two trial arms and an adjustment to the definition of the primary endpoint. If the STREAM experimental regimens are shown to be non-inferior or superior to the stage 1 study regimen, this would represent an important contribution to evidence about potentially more tolerable and more efficacious MDR-TB regimens, and a welcome advance for patients with rifampicin-resistant tuberculosis and tuberculosis control programmes globally. Trial registration: ISRCTN ISRCTN18148631 . Registered 10 February 2016